2009
DOI: 10.1007/s00232-009-9210-4
|View full text |Cite
|
Sign up to set email alerts
|

FXYD2 and Na,K-ATPase Expression in Isolated Human Proximal Tubular Cells: Disturbed Upregulation on Renal Hypomagnesemia?

Abstract: Autosomal dominant renal hypomagnesemia (OMIM 154020), associated with hypocalciuria, has been linked to a 121G to A mutation in the FXYD2 gene. To gain insight into the molecular mechanisms linking this mutation to the clinical phenotype, we studied isolated proximal tubular cells from urine of a patient and a healthy subject. Cells were immortalized and used to assess the effects of hypertonicity-induced overexpression of FXYD2 on amount, activity and apparent affinities for Na+, K+ and ATP of Na,K-ATPase. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, other reports suggest that it may function independently as an inward rectifier channel (464). Functional analysis of the patient's proximal tubular cells showed no differences in Na ϩ , K ϩ , or ATP affinity of the Na ϩ -K ϩ -ATPase, but demonstrated a lower FXYD2 protein expression (67). I) HNF1B.…”
Section: Genetic Hypomagnesemiamentioning
confidence: 80%
“…However, other reports suggest that it may function independently as an inward rectifier channel (464). Functional analysis of the patient's proximal tubular cells showed no differences in Na ϩ , K ϩ , or ATP affinity of the Na ϩ -K ϩ -ATPase, but demonstrated a lower FXYD2 protein expression (67). I) HNF1B.…”
Section: Genetic Hypomagnesemiamentioning
confidence: 80%
“…In relation to the hypothesis raised here, it seems possible that, over time, the lack of association with FXYD2 G41R and loss of stabilization of ␣␤ subunits reduces the density of pumps in the distal convoluted tubule, thereby compromising the ability of the cell to maintain the driving force for active Mg 2ϩ transport (trans-epithelial voltage, Na ϩ gradients). A recent paper reports that induction of FXYD2 in human proximal tubule cells by hypertonic media is associated with increased Na,K-ATPase activity and ␣ subunit expression, but the increase in Na,K-ATPase activity and ␣ subunit density is blunted in the cells from patients with the G41R mutation, thus associating the two phenomena (62). Another example has been described in connection with mice deficient in FXYD1.…”
Section: Discussionmentioning
confidence: 99%
“…There are also several genes for the β subunit ( ATP1B1, ATP1B2, ATP1B3 ) [16]. The γ subunit is coded for by FXYD2 [17]. Mutations in FXYD2 result in hypomagnesemia and hypocalciuria [17].…”
Section: Thiazide Diureticsmentioning
confidence: 99%
“…The γ subunit is coded for by FXYD2 [17]. Mutations in FXYD2 result in hypomagnesemia and hypocalciuria [17]. In-vitro studies have shown that the Na,K-ATPase is regulated by phosphorylation on the α subunit by protein kinase A (PKA) and protein kinase C (PKC) [1820].…”
Section: Thiazide Diureticsmentioning
confidence: 99%